(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Prostate cancer (PCa) is the predominant form of internal cancer found in males and ranks as the second most prevalent cause of cancer-related mortality in Western countries. The ubiquitin-conjugating enzyme (E2) and ubiquitin specific peptidase (USP22) play a crucial role in regulating protein post-translational modification. The deregulation of the ubiquitin system is linked to several disorders, including cancer, and is implicated in PCa. The study aimed to determine serum E2andUSP22 concentration and relate it to the risk of developing PCa and to assess mitochondrial DNA by RT-qPCR. Methods: The study was conducted in October 2023 to February 2024. The study included 60 men diagnosed with PCa by their physicians and a total of 60 individuals who were in good health and had no prior medical history of PCa. A 5 mL of blood were withdrawn from patients and controls groups. The blood urea ,creatinine and PSA was don. The serum Ubiquitin conjugating enzyme (E2), Ubiquitin specific peptidase22 (USP22) were measured by ELISA and mitochondrial DNA (mtDNA) was assessed by qPCR. Results: The study results showed a significant difference (P=0.0011) in PSA levels between patients and the control group. Based on the research data, serum E2 levels of patients with PCa were significantly elevated compared to the control groups (P≤ 0.01). The serum USP22 levels of patients with PCa were significantly greater than those of the control groups , with a statistically significant rise observed in the PCa patients compared to the control group (P ≤ 0.01).The patient group exhibited significantly greater levels of whole blood mtDNA synthesis compared to the control group (P ≤ 0.01). Conclusions: Increase E2 , USP22 seems to have an significant role in the progress of PCa. Increased mtDNA synthesis in patients with PCa as consequences of mtDNA variants and replication.